Climate change, farm size and land use in Brazilian Legal Amazon - Ferreira, Marcelo Dias Paes (2015)
Brazilian Legal Amazon is strategic to Brazilian environmental and social achievements and land use plays an important role in this context. This study aimed to assess how climate change and farm size would affect the land use pattern in this region. We developed two chapters to address these issues: Climate Change, Climate Risk and Land Use in Brazilian Legal Amazon and Farm Size and Land Use Efficiency in Brazilian Legal Amazon. In the first chapter, we set up a risk-averse land use model. Results pointed out that the amount of rainfall, inter-annual temperature variance and inter-annual rainfall variance are associated to land use allocation in Brazilian Legal Amazon. There is evidence that farmers are risk-averse and the establishment of pasture is positively associated to rainfall risk. Our climate change simulations indicate that there will be re-allocation of land from forest and crops to pasture. Depending on the increase in climate variability and time horizon, deforestation ratios range between 10% to 16% of total forest areas. In the second chapter, we measure land use efficiency and technical efficiency by Stochastic Frontier Analysis. We found that farm size is negatively associated to the productivity measures. Therefore, larger farms are less productive and waste more land than smaller farms.